Checkpoint: An innovative Programme to navigate people away from the cycle of reoffending – A randomised control trial evaluation. (September 2022) - Weir, Kevin; Kilili, Stephanie; Cooper, John; Crowe, Andrew; Routledge, Gillian
This study contributes to the evidence base of police deferred prosecution schemes aimed at reducing reoffending. Durham Constabulary, UK, introduced Checkpoint, an adult deferred prosecution scheme which targets offenders entering the Criminal Justice System by providing an alternative to a criminal prosecution. Applying theories of deterrence and desistance, this paper describes the randomised control trial findings of 521 offenders randomised between 1 August 2016 and 31 March 2018. The results indicate that the Checkpoint treatment cohort achieved a lower reoffending rate in comparison to the control cohort, on the basis of prevalence (10.3% reduction) and risk of reoffending (30% reduction).